2012
DOI: 10.1364/ao.52.00a290
|View full text |Cite
|
Sign up to set email alerts
|

Fast polygon-based method for calculating computer-generated holograms in three-dimensional display

Abstract: In the holographic three-dimensional (3D) display, the numerical synthesis of the computer-generated holograms needs tremendous calculation. To solve the problem, a fast polygon-based method based on two-dimensional Fourier analysis of 3D affine transformation is proposed. From one primitive polygon, the proposed method calculates the diffracted optical field of each arbitrary polygon in the 3D model, where the pseudo-inverse matrix, the interpolation, and the compensation of the power spectral density are emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Computation of a polygon field is slower than that of a spherical wave emitted by a point light source, but the number of polygons is much smaller than that of point sources and the total computation time is shorter compared to the point cloud approach. The traditional polygon-based method evolved to analytical implementation when the angular spectrum of a triangle of arbitrary size, shape, orientation and location in space is analytically calculated from the known spectrum of a reference triangle [38][39][40]. The analytical method eliminates the need to apply FFT for each polygon.…”
Section: Methods For Computer Generation Of Holographic Fringe Patternsmentioning
confidence: 99%
“…Computation of a polygon field is slower than that of a spherical wave emitted by a point light source, but the number of polygons is much smaller than that of point sources and the total computation time is shorter compared to the point cloud approach. The traditional polygon-based method evolved to analytical implementation when the angular spectrum of a triangle of arbitrary size, shape, orientation and location in space is analytically calculated from the known spectrum of a reference triangle [38][39][40]. The analytical method eliminates the need to apply FFT for each polygon.…”
Section: Methods For Computer Generation Of Holographic Fringe Patternsmentioning
confidence: 99%
“…The research reported in Refs. [38,39] performed only a single FFT operation on a reference triangle rather than repeated FFT operations for every triangle to reduce the computation time. The local angular spectrum for an arbitrary triangle is obtained by resampling the obtained discrete local angular spectrum of the reference triangle considering the geometric relationship between the given and reference triangles.…”
Section: Triangular-mesh-based Synthesismentioning
confidence: 99%
“…Although many researchers have developed various accelerating methods [2][3][4], to achieve the solid effect, the point-based method needs tremendous computation. The polygon-based method is expected to be the fast computation method since it represents the 3D objects by many polygons, by which the amount of the computation unit is significantly decreased [5][6][7][8][9][10][11][12][13][14][15]. In addition, combining with the rendering algorithms of the computer graphics, the polygon-based method could easily add texture and shade to the 3D scene.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been four main approaches under the PWD frame: the traditional polygon-based method [5][6][7][8][9][10], the full analytical method [11,12], the spatial approximate method [13,14], and the 3D affine transformation method [15]. The traditional method depicts the tilted polygon in its local coordinates, computes the corresponding Fourier spectrum, calculates the new frequency from the spatial 3D rotational transformation and rotates the spectrum to the global coordinates by the interpolation approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation